CONSTRAINTS ON CREDIT, CONSUMER BEHAVIOUR AND THE DYNAMICS OF WEALTH - Costa Gomes, Orlando (Economic Annals, 2009)
This paper develops a simple macroeconomic model where the pattern of wealth accumulation is determined by a credit multiplier and the way households react to short-term fluctuations. Given this setup, long term wealth dynamics are eventually characterized by the presence of endogenous cycles.